Pulmonary hypertension is associated with an increased incidence of cancer diagnoses. (27th June 2022) - Roderburg, Christoph; Loosen, Sven H.; Hippe, Hans‐Joerg; Luedde, Tom; Kostev, Karel; Luedde, Mark
Abstract: Pulmonary hypertension (PH) is a complex disease with increasing global incidence that eventually leads to right ventricular failure and is associated with a poor prognosis. The importance of noncardiac comorbidities in disease progression and prognosis has gained increasing recognition in recent years. In the present study, we investigated a potential association between PH and cancer in an outpatient cohort in Germany. Using the IQVIA Disease Analyzer database, we identified a total of 11, 109 patients with PH and a propensity score matched cohort of equal size without PH who received medical treatment between 2005 and 2019. Logistic regression models were used to evaluate the potential association between PH and cancer. Within the 10‐year observation period, the incidence of cancer was significantly higher in PH patients than non‐PH patients (23.2% vs. 8.5%, log‐rank p  < 0.001). Importantly, this association was observed for both male (HR = 1.24, p  = 0.002) and female (HR = 1.37, p  < 0.001) patients, and was most pronounced in patients >80 years (HR = 1.50, p  <  0.001). In terms of a specific tumor site, we found a significant association for respiratory organ cancer (HR = 1.60, p  = 0.007) and skin cancer (HR = 1.48, p  < 0.001). Our study provides strong evidence that PH is associated with an increased incidence of cancer. This finding should help raise awareness of this important comorbidity and could trigger specific screening programs in patients with PH.